PERAN GURU PAI DALAM MEMBENTUK KARAKTER ISLAMI SISWA MELALUI PROGRAM TAḤFIḌ AL-QUR’AN DI SEKOLAH MENENGAH PERTAMA BIRRUL WALIDAIN MUHAMMADIYAH SRAGEN - Fuad Abdul Manaf; M. Darojat Ariyanto (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2020)
Birrul Walidain Middle School Muhammadiyah Sragen is one of Muhammadiyah's Integrated Islamic schools in Cantel Wetan, Sragen. The purpose of this study is to describe Islamic-based school programs and relate them to the presence of students with Islamic characteristics. The type of research used is field research (field research) and data collection techniques with the process of collecting documents, interviews, observations, (field observations), data analysis, and data validity.The result of this research is that the Tafiḍ Al-Qur'an Activity Program in Birrul Walidain Junior High School Muhammadiyah Sragen is one of the efforts of teachers and educators to shape Islamic character in each student's personality and create a generation of Qur'anic and Intelligent Achievers (Intellectual). and Spirituality), so as to be able to become someone who is honest, fair, disciplined (worship and learning), patient, and trustworthy in carrying out every activity responsibility. The students are considered ready spiritually and physically to be directed and formed with Islamic character education and morals.